Intelligent web-based E-learning system - K, Deepa; P, Gangeswar; M, Manikandan; C, Charulatha (International Journal of Engineering and Technology, 2018)
This paper is based on Web Application and it is host on the cloud web server. The main theme of that paper is study oriented material are bind to form the single website. It is mainly used for students to refer there departmentâ€™s major paper oriented topic. This paper severs in the way of a video tutorial, presentation and relevant edition of book. It can be categories into a different part of languages C, C++, JAVA, database, computer networks etc. Whatever area the user wants they can be searched to use that material. There are three categories of user they are an admin, moderator and visitor. Admin having all permission to view the detail of the users. This will help to know what requirement the user needs. The visitor is a general user to visit the website to surf the study content and having some doubt about the subject they permit to post on that site. Moderator is the intermediate between the admin and the visitor, they have to upload the videos and presentation content and have to reply the posted questions also. The web framework was developed with the help of python-Django 1.11.1. It is one of the web frameworks that has inbuilt module and API. The user gets login with the help of Google authentication. In that way they detail can be stored in the database. Sqlite3 version database is used for fast retrieving and storing the data. The front end of this project is using HTML, CSS, and JavaScript. This will provide the good user-interface. The hijacker module is used to improvise the search content.Â Â